2012
DOI: 10.1039/c2lc21006a
|View full text |Cite
|
Sign up to set email alerts
|

Studies of bacterial aerotaxis in a microfluidic device

Abstract: Aerotaxis, the directional motion of bacteria in gradients of oxygen, was discovered in late 19th century and has since been reported in a variety of bacterial species. Nevertheless, quantitative studies of aerotaxis have been complicated by the lack of tools for generation of stable gradients of oxygen concentration, [O2]. Here we report a series of experiments on aerotaxis of Escherichia coli in a specially built experimental setup consisting of a computer-controlled gas mixer and a two-layer microfluidic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 65 publications
(182 reference statements)
4
57
0
Order By: Relevance
“…Note that this response is highly unlikely to be an aerotactic response through Aer, as strains lacking a functional Tsr receptor did not show any response in the microfluidic assay. Moreover, the device is not designed to either generate or maintain gaseous gradients within the flow chamber, as has been reported by Adler et al (30). Chemotaxis to DHMA requires the Tsr chemoreceptor and its intact serine-binding site.…”
Section: Resultsmentioning
confidence: 90%
“…Note that this response is highly unlikely to be an aerotactic response through Aer, as strains lacking a functional Tsr receptor did not show any response in the microfluidic assay. Moreover, the device is not designed to either generate or maintain gaseous gradients within the flow chamber, as has been reported by Adler et al (30). Chemotaxis to DHMA requires the Tsr chemoreceptor and its intact serine-binding site.…”
Section: Resultsmentioning
confidence: 90%
“…This behavior, called taxis [Krell et al, 2011, Purcell, 1977, has long been a subject of scientific investigation, as it serves a variety of purposes: seeking out nutrients and avoiding toxic substances Armitage, 2004, Adler, 1969], identifying thermal [Paster and Ryu, 2007] and oxygen [Adler et al, 2012] gradients, as well as aiding pathogenic species in infecting their hosts [Rivera-Chávez et al, 2013, Cullender et al, 2013. The understanding of bacterial taxis is not only important when it comes to bacterial motility and accumulation; it also serves as a model for biological signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, one can take advantage of the gas permeability of PDMS to create steady oxygen gradients without the need for hydrogels or membranes (Adler et al 2010). This principle used by Adler et al (2012), who studied aerotaxis in E. coli under steady, linear profiles of oxygen ranging from microaerobic to aerobic conditions and showed that it does not obey log-sensing. Furthermore, the irreversible bonding that can be achieved between layers of PDMS, but not with hydrogels, makes aerotaxis an ideal model system for the study of microbial navigation in more realistic environments, such as when fluid flow is present.…”
Section: Microbial Navigationmentioning
confidence: 99%